Nonsurgical cerebrospinal fluid rhinorrhea in invasive macroprolactinoma: incidence, radiological, and clinicopathological features. - Suliman, S; Gurlek, A; Byrne, J; Sullivan, N; Thanabalasingham, G; Cudlip, S; Ansorge, O; Wass, J (2007)
CONTEXT: Macroprolactinomas (MPRLs) may result in nonsurgical (spontaneous or dopamine agonist induced) cerebrospinal fluid (CSF) rhinorrhea; however, the incidence of and mechanisms underlying this phenomenon are poorly understood. OBJECTIVE: The objective of the study was to determine the incidence of nonsurgical rhinorrhea and identify biochemical, radiological, and histopathological factors associated with leakage. DESIGN, SETTING, AND PARTICIPANTS: A retrospective review of MPRL patients (n = 114) was compared with patients with nonfunctioning pituitary adenoma (NFA) (n = 181) seen over a 19-yr period (1985-2004). MAIN OUTCOME MEASURES: Incidence of CSF rhinorrhea, factors predictive of leakage, and differential expression of candidate markers of invasiveness were measured. RESULTS: Nonsurgical CSF rhinorrhea occurred in 8.7% of MPRLs (10 of 114) [2.6% spontaneous (three of 114), 6.1% dopamine agonist induced (seven of 114)], whereas no NFAs developed nonsurgical rhinorrhea. There was a clear male preponderance in MPRLs with nonsurgical rhinorrhea (males to females, 9:1, P = 0.008). Dopamine agonist resistance was more frequent in MPRLs with rhinorrhea than with MPRLs without rhinorrhea [30% (n = 10) vs. 5% (n = 104) P = 0.003]. Baseline prolactin levels, rate of prolactin decline in response to dopamine agonists, and tumor volume at diagnosis did not predict CSF leakage. Candidate markers of invasiveness, specifically the protease-activated receptor 1 and e-cadherin expression scores and tumor macrophage density, were not significantly different between groups; MPRL+CSF rhinorrhea (n = 6), MPRL without CSF rhinorrhea (n = 9), and NFAs (n = 9). CONCLUSIONS: The incidence of nonsurgical CSF rhinorrhea in MPRL patients (8.7%) is higher than expected. Dopamine agonist resistance is more common in MPRLs with CSF rhinorrhea; however, whether this is a mechanistic relationship requires further study. Protease-activated receptor 1 expression, e-cadherin expression, and macrophage infiltration rates do not distinguish tumors with from those without CSF rhinorrhea.